The antioxidant status of coenzyme Q10 and vitamin E in children with type 1 diabetes - Usama M. Alkholy; Nermin Abdalmonem; Ahmed Zaki; Mohamed A. Elkoumi; Mustafa I. Abu Hashim; Maha A.A. Basset; Hossam E. Salah (Jornal de Pediatria, 2019)
Objective: The purpose of this study was to evaluate the antioxidant status of plasma vitamin E and plasma and intracellular coenzyme Q10 in children with type 1 diabetes. Method: This case–control study was conducted on 72 children with type 1 diabetes and compared to 48 healthy children, who were age, sex, and ethnicity-matched. The diabetic children were divided according to their glycosylated hemoglobin (A1c %) into two groups: poor and good glycemic control groups. All children underwent full history taking, clinical examination, and laboratory measurement of complete blood count, A1c %, plasma cholesterol, triglycerides, and vitamin E levels and coenzyme Q10 levels in plasma, erythrocytes, and platelets. Results: Children with poor glycemic control showed significantly higher plasma vitamin E, coenzyme Q10, triglycerides, low-density lipoproteins, waist circumference/height ratio, cholesterol levels, and lower high-density lipoproteins and platelet coenzyme Q10 redox status in comparison to those with good glycemic control and the control group (p < 0.05). Plasma coenzyme Q10 showed a positive correlation with the duration of type 1 diabetes, triglycerides, cholesterol, vitamin E, and A1c %, and negative correlation with the age of the diabetic group (p < 0.05). The platelet redox status showed a negative correlation with the A1c % levels (r = −0.31; p = 0.022) and the duration of type 1 diabetes (r = −0.35, p = 0.012). Conclusion: Patients with type 1 diabetes, especially poorly controlled, had elevation of plasma vitamin E and coenzyme Q10 levels and decreased platelet redox status of coenzyme Q10, which may be an indicator of increased oxidative stress. Resumo: Objetivo: Avaliar o estado antioxidante da vitamina E no plasma e da coenzima Q10 no plasma e intracelular em crianças com diabetes tipo 1. Método: Este estudo caso-controle foi realizado em 72 crianças com diabetes tipo 1 comparadas comparado por idade, sexo e etnia de 58 crianças saudáveis. As crianças diabéticas foram divididas em dois grupos de acordo com sua hemoglobina glicosilada (A1c %): grupos de controle glicêmico bom e baixo. Todas as crianças foram submetidas a anamnese total, exame clínico e laboratorial para hemograma completo, A1c %, colesterol no plasma, triglicerídeos e níveis de vitamina E e níveis de coenzima Q10 no plasma, eritrócitos e plaquetas. Resultados: As crianças com baixo controle glicêmico mostraram nível de vitamina E no plasma significativamente maior, coenzima Q10, triglicerídeos, lipoproteína de baixa densidade, proporção da circunferência da cintura/estatura e níveis de colesterol e menor nível de lipoproteína de alta densidade e estado redox da coenzima Q10 em comparação aos com bom controle glicêmico com o grupo de controle (p < 0,05). A coenzima Q10 no plasma mostrou correlação positiva com a duração da diabetes tipo 1, triglicerídeos, colesterol, vitamina E e A1c % e correlação negativa com a idade do grupo diabético (p < 0,05). O estado redox das plaquetas mostrou correlação negativa com os níveis de A1c % (r = -0,31; p = 0,022) e a duração da diabetes tipo 1 (r = -0,35, p = 0,012). Conclusão: Os pacientes com diabetes tipo 1, principalmente mal controlados, apresentaram aumento nos níveis de vitamina E no plasma e coenzima Q10 e redução no estado redox das plaquetas da coenzima Q10 que podem indicar aumento do estresse oxidativo. Keywords: Type 1 diabetes, Oxidative stress, Vitamin E, Coenzyme Q10, Palavras-chave: Diabetes tipo 1, Estresse oxidativo, Vitamina E, Coenzima Q10